Schizophrenia: An Impairment in the Capacity to Perceive Affordances - Kim, Nam-Gyoon; Kim, Hakboon (Frontiers in Psychology, 2017)
Phenomenological psychopathologists conceptualize schizophrenia as a self-disorder involving profound distortions of selfhood. For James Gibson, “to perceive the world is to coperceive oneself.” If the sense of self is disturbed in individuals with schizophrenia, this could also lead to disturbances in these individuals’ ability to perceive affordances, environmental properties taken with reference to the perceiver’s action capabilities (e.g., a rigid surface affording ‘walk-on-able,’ chairs ‘sit-on-able,’ and so on). To test this hypothesis, three experiments investigated schizophrenia patients’ affordance perception. Participants were presented with a photo of a common object on the computer and then asked to judge its secondary affordance (a non-designed function) in a two-choice reaction time task in Experiment 1 and in a yes/no task in Experiment 2. Schizophrenia participants performed less accurately and more slowly than controls. To rule out visual impairment as a contributing factor, in Experiment 3, participants identified physical properties (color, shape, material composition) of the objects. Schizophrenia participants were as accurate as controls and responded faster than in the previous experiments. Results suggest that the capacity to perceive affordances is likely impaired in people with schizophrenia, although the capacity to detect the object’s physical properties is kept intact. Inability to perceive affordances, those functionally significant properties of the surrounding environment, may help explain why schizophrenia patients may appear as somewhat detached from the world.